Amyloid β deposition in subcortical stroke patients and effects of educational achievement: A pilot study. (31st July 2019) - Yasuno, Fumihiko; Kajimoto, Katsufumi; Ihara, Masafumi; Taguchi, Akihiko; Yamamoto, Akihide; Fukuda, Tetsyuta; Kazui, Hiroaki; Iida, Hidehiro; Nagatsuka, Kazuyuki
Abstract : Objective: A direct causal relationship of cerebrovascular risk factors/stroke to amyloid β (Aβ) deposition has yet to be shown. We conducted [ 11 C] Pittsburgh compound B (PiB)–positron emission tomography (PET) analysis on subacute ischemic stroke patients and healthy controls. We hypothesized that subacute ischemic stroke patients would show focal Aβ accumulation in cortical regions, which would increase and extend over time during the chronic phase after stroke onset. Methods: Patients were recruited 14 to 28 days after acute subcortical ischemic stroke and examined with [ 11 C]PiB‐PET scans. Regional time‐activity data were analyzed with the Logan graphical method. Whole brain voxel‐based analysis was conducted to compare stroke patients with healthy controls. We also performed longitudinal comparison of patients with successive [ 11 C]PiB‐PET scans 1 year after stroke. Results: Voxel‐based analysis revealed a significant increase of [ 11 C]PiB‐BPND of the precuneus/posterior cingulate cortex (PCu/PCC) in stroke patients at the subacute stage. Based on stepwise multiple regression analysis of [ 11 C]PiB‐BP changes during follow‐up as the dependent variable, years of education was the best independent correlate. There was a significant negative relationship between changes in [ 11 C]PiB‐BP and years of education. Conclusions: Our results suggest that processes before and after the onset of ischemic stroke may trigger Aβ deposition in the PCu/PCC, whereby amyloid deposition begins at an early stage of Alzheimer's disease (AD). Our findings support the existence of a cooperative association between vascular risk factors/stroke and AD progression. Further, educational achievement had a protective effect against the increase in Aβ accumulation.